Chemical atributes of an oxisol submitted to weed control in coffee - Siqueira, Raphael Henrique da Silva; Ferreira, Mozart Martins; Alcântara, Elifas Nunes de; Silva, Raphael Comanducci (Coffee Science - ISSN 1984-3909, 2015)
In coffee culture, the inadequate control of invasive plants can degrade the soil used then managements practices to contribute to the improvement of quality physical, chemical and biological of the soil. Should be used the aim of this work were evaluated the influence of various weed control methods on some chemical properties of a Red-Yellow Latosol (RYL) cultivated with coffee. The experimental design was randomized block with strip plots, making a 9x2 factorial, nine control methods and two layers (0-15 and 15-30 cm) and three replications. The control methods evaluated were: maintenance of soil cover with forrage peanut (Arachis pintoi L.) and Signal grass (Brachiaria decumbens), use of disk harrow, mower, agricultural brush, manual hoe, post-emergency herbicide, pre-emergence herbicide and no weeding treatment. The following chemical analyzes were performed: pH, exchangeable cations of sorption complex, sum of bases, base saturation, aluminum saturation, effective cation exchange capacity, potential cation exchange capacity, soil organic matter, total phosphorus and remanescent phosphorus. Among the weed control methods studied, the use of mower provided the best soil chemical characteristics at the two layers evaluated. The pre-emergence herbicide remained the surface of the soil devoid cover, wich negatively influenced the soil chemical attributes, by increasing the acidity and reduced cations of the sorption complex. The Signal grass showed higher efficiency than the forrage peanut in the management of alkaline front, although the latter was more efficient in phosphorus cycling.